CENTRAL DURAL TENTING SUTURES IN A PATIENT WITH TRAUMATIC ACUTE EPIDURAL HEMATOMA: A CASE REPORT - Marković, Aleksandar; Ilić, Jovan; Stefanović, Ivan; Nikolov, Vesna; Radisavljević, Miša; Kovačević, Jelena; Stojanović, Nikola; Djordjević, Marija (Acta medicae Medianae, 2023)
It is of paramount significance to diagnose epidural hematoma (EDH) as soon as possible and to evacuate EDH if necessary. Our aim was to show the importance of placing prophylactic central dural tenting sutures (DTS) for ensuring adequate hemostasis. We present a case of a 62-year-old male patient, who was diagnosed with an acute traumatic EDH and cerebral hemorrhagic contusion. The postoperative course was complicated by deterioration of the patient's consciousness and worsening of the left-sided hemiparesis, therefore we performed a head CT scan, which showed the formation of the new EDH at the operating site. Moreover, we reoperated the patient with the placement of multiple central DTS, while the control head CT scan showed a complete evacuation of the EDH. Consequently, the patient made a good recovery at discharge, with a remaining discrete left-sided hemiparesis. Prophylactic central DTS are important for maintaining an adequate hemostasis while operating on patients with EDH.
Keywords: epidural hematoma, dural tenting suture